Host-derived nitrate boosts growth of E. coli in the inflamed gut - Winter S.E. (2014)
Changes in the microbial community structure are observed in individuals with intestinal inflammatory disorders. These changes are often characterized by a depletion of obligate anaerobic bacteria, whereas the relative abundance of facultative anaerobic Enterobacteriaceae increases. The mechanisms by which the host response shapes the microbial community structure, however, remain unknown. We show that nitrate generated as a by-product of the inflammatory response conferred a growth advantage to the commensal bacterium Escherichia coli in the large intestine of mice. Mice deficient in inducible nitric oxide synthase did not support the growth of E. coli by nitrate respiration, suggesting that the nitrate generated during inflammation was host-derived. Thus, the inflammatory host response selectively enhances the growth of commensal Enterobacteriaceae by generating electron acceptors for anaerobic respiration.